Efficacy and safety of oral semaglutide in Russian patients with type 2 diabetes: subgroup analysis of PIONEER 1, 2, 3 trials - M. Sh. Shamkhalova; M. V. Shestakova (Сахарный диабет, 2022)
INTRODUCTION. Glucagon-like peptide-1 receptor agonists (GLP-1 RA) are the treatment options with comprehensive action on different aspects of type 2 diabetes. Due to its peptide nature GLP-1 RAs, until recent time the delivery of these agents into patients’ organism was via injectable devices. In 2019, the first time in history oral semaglutide was registered based on the results of PIONEER clinical trial program, since 2021 this drug is available in Russia. However, the pathophysiology of type 2 diabetes and local treatment approaches may differ in different populations; this can lead to the differences in the efficacy and safety of newly registered drug. Therefore, it is necessary to evaluate the response in different populations. In this paper we report the result of subanalysis of efficacy and safety of oral semaglutide in Russian patients.OBJECTIVE. The aim of this analysis is to evaluate efficacy and safety of oral semaglutide in Russian patients, who participated in semaglutide clinical development program, as well as to evaluate consistency and applicability of the results obtained from global population in that program.MATERIALS AND METHODS. Patients from PIONEER 1, 2, 3 were included in the analysis: 150 patients from Russian, 1956 — the rest patients from these trials. Reductions in HbA1c and body weight were analyzed in both cohorts, and treatment differences were tested for interaction. Similarly, the rate of adverse events was analyzed.RESULTS. Reduction in HbA1c in oral semaglutide arms in both cohorts showed numerically similar and consistent result. Interaction test showed statistical difference in PIONEER 1 data (p=0.0268) — the effect was due to diminishing influence of substantial response in placebo arm in Russian cohort. In longer-term trials (PIONEER 2 and 3) this finding was not confirmed (p=0.7459 and p=0.4906, respectively). In regard to body weight reduction there were more numerically pronounced results in Russian cohort compared to global population; although statistical significance were not reached in any of the trial (p>0.05). There was lower rate of reported adverse events in Russian patients compared to the rest cohort.CONCLUSION. This analysis showed similar efficacy and safety of oral semaglutide in Russian patients compared to global population of patients from clinical program.